Mulheres em movimento : Relações de gênero na comunidade Quilombola Buriti do Meio no Norte de Minas Gerais/Brasil - Aguiar, Wanderleide Berto ([Actas])
In a civilisation space of Sao Francisco basin river. Women and men interlace on their relations building mutual and each one on your way in handling of the clay in politics fights and in life daily of Buriti do Meio Quilombo. The objective of this study was to do a ethnographically reflection of gender relations that link men and women in the black rural community Buriti do Meio in Sao Francisco municipal district on the North of Minas Gerais/Brazil. We tried to understand the meanings and the composed representations on the feminineness and the masculine ways in relation that men and women set up among themselves in handling workmanship for the information in politics fight of community group as quilombo remaining and to rights access derived and everyday life where they build and organize together the life of all their members reflecting in his symbolic order. Buriti do Meio is traditional known for its handcraft and for cultural manifestations, legacy of their ancestral, olds slaves that ran way to look for autonomy and freedom express signs of afrobrazilian culture inserted on the civilization space in Sao Francisco basin river